Method for preparing high-purity hydrogen through waste plastic self-derived carbon nanotube reinforced microwave effect
By using self-derived carbon nanotube-loaded multi-nano-metal particle catalyst and microwave heating technology in the production of waste plastic hydrogen, problems such as low yield and low purity in the existing technology are solved, and efficient preparation of high-purity hydrogen is achieved.
Patent Information
- Application Number
- CN202411759661.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-03
Smart Images

Figure CN119569042A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid waste treatment, and in particular to a method for preparing high-purity hydrogen by using waste plastic self-derived carbon nanotubes to enhance microwave effect. Background Art
[0002] Plastics are widely used in agriculture, commerce, transportation, and medical industries due to their ductility, lightness, durability, and low price. At present, global plastic consumption has surged to 390.7 million tons in 2021, a twenty-fold increase over the previous fifty years. However, the inherent toxicity of plastics and improper handling pose a serious threat to public health and socioeconomic development. Therefore, it is crucial to establish a sustainable waste plastic treatment and disposal system. Secondly, the chemical composition of plastics is usually rich in elements such as carbon, hydrogen, and oxygen. The combination of these elements gives plastics a high energy density and great energy potential. However, at present, less than 10% of plastic waste in the world can be recycled. In order to further treat plastics harmlessly and make full use of the carbon and hydrogen elements in their substances, it is necessary to develop waste resource utilization technology. Existing plastic resource conversion technologies mostly take liquid products as the main production target, but the economic efficiency and energy calorific value of liquid pyrolysis oil are low. Future technologies should pay more attention to the production of high value-added products, especially the generation of clean energy such as hydrogen. Microwave pyrolysis has become an effective technology for gas phase conversion of waste plastics and hydrogen generation because it can directly act on the molecular level, reduce heat loss, have a higher reaction rate, more uniform heating effect and lower energy consumption. However, the existing hydrogen production of waste plastics based on microwave pyrolysis still faces technical bottlenecks such as low output and low purity. Summary of the invention
[0003] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one object of the present invention is to provide a method for catalyzing waste plastics with self-derived carbon nanotubes loaded with multi-element nano-metal particles and enhancing microwave effect, wherein the hydrogen generated by the method has high yield and purity.
[0004] To this end, the first aspect of the present invention provides a method for preparing high-purity hydrogen by strengthening microwave effect from self-derived carbon nanotubes of waste plastics, comprising: S1, mixing plastics and multi-component nano-metal catalysts, adding microwave absorbers, and obtaining a mixture, wherein the multi-component nano-metal catalysts include Ni, Al, and Fe; S2, heating the mixture by microwaves in an inert gas to obtain hydrogen and self-derived carbon nanotubes; S3, reloading the self-derived carbon nanotubes with the multi-component nano-metal catalysts, adding them in step S1, and microwave heating and reacting in S2 to obtain hydrogen. The method for preparing hydrogen from self-derived carbon nanotubes of waste plastics proposed by the present invention further increases the hydrogen production by more than 20%, reaching 62.55 mmol / g, and the hydrogen purity is greater than 90 vol%.
[0005] The method for preparing high-purity hydrogen from self-derived carbon nanotubes of waste plastics proposed in the present invention adopts microwave heating. First, a multi-component nano-metal catalyst containing Ni, Al and Fe is used to react the plastic in an oxygen-free environment. Microwaves are used to increase the temperature of the internal particles, thereby promoting molecular motion and heat transfer by forming a local temperature increase area, thereby obtaining a higher yield of gas products and a high value-added solid product. In addition, the solid product carbon nanotubes formed after microwave heating of the plastic can also be used as a carrier of the multi-component nano-metal catalyst after activation and purification, and have a stronger microwave absorption effect, catalytic activity and stability, so that the hydrogen yield and purity are further improved. This self-derived carbon nanotube multi-component nano-metal particle catalyst can be recycled ten times and has a high economic value.
[0006] In some embodiments of the present invention, the microwave absorber includes at least one of silicon carbide, activated carbon, graphite, and carbon black.
[0007] In some embodiments of the present invention, the mass ratio of the plastic to the microwave absorber is 1:(2-10).
[0008] In some embodiments of the present invention, the particle size of the microwave absorber is 3 mm-10 mm.
[0009] In some embodiments of the present invention, the mass ratio of the multi-element nano-metal catalyst to the plastic is 1:(0.5-2.5).
[0010] In some embodiments of the present invention, in the multi-element nanometal catalyst, the molar ratio of Ni, Al and Fe is 1:(1-5):(1-5).
[0011] In some embodiments of the present invention, the multi-element nano-metal catalyst is prepared by the following method: dissolving soluble nickel salt, soluble aluminum salt and soluble iron salt in water, adding a chelating agent, heating and stirring to form a gel; drying and calcining the gel to obtain a multi-element nano-metal catalyst.
[0012] In some embodiments of the present invention, the chelating agent includes at least one of citric acid, urea, polyethylene glycol, and ethylenediaminetetraacetic acid.
[0013] In some embodiments of the present invention, the heating temperature is 80°C-120°C.
[0014] In some embodiments of the present invention, the stirring time is 2h-6h.
[0015] In some embodiments of the present invention, the calcination temperature is 350°C-650°C.
[0016] In some embodiments of the present invention, the mass ratio of the soluble nickel salt, the soluble aluminum salt and the soluble iron salt is 1:(1-8):(1-8)
[0017] In some embodiments of the present invention, the power of the microwave heating is 1 kW-3 kW.
[0018] In some embodiments of the present invention, the temperature of the microwave heating is 450°C-750°C.
[0019] In some embodiments of the present invention, the microwave heating time is 10 min-50 min.
[0020] In some embodiments of the present invention, step S2 includes: S21, heating the mixture by microwave in an inert gas to obtain a hydrogen mixed gas, a solid product, and a liquid oil; S22, treating the solid product with an acid solution, washing it to neutrality, and then treating it with an alkaline solution, washing it to neutrality to obtain activated carbon nanotubes; step S3 includes: S31, dissolving a soluble nickel salt, a soluble aluminum salt, and a soluble iron salt in water, adding the activated carbon nanotubes, adding a chelating agent, heating and stirring to form a gel; S32, drying and calcining the gel to obtain a self-derived carbon nanotube-loaded multi-nanometallic catalyst; S33, using the self-derived carbon nanotube multi-nanometallic catalyst in steps S1 and S21 to further prepare high-purity hydrogen.
[0021] In some embodiments of the present invention, the mass of the activated carbon nanotubes accounts for 10% to 40% of the mass of the multi-nanometallic catalyst.
[0022] In some embodiments of the present invention, the activated carbon nanotubes have a cup-stacked morphology.
[0023] In some embodiments of the present invention, in step S22, the acid solution includes at least one of concentrated nitric acid, concentrated sulfuric acid, and hydrochloric acid.
[0024] In some embodiments of the present invention, in step S22, the alkaline solution includes at least one of a sodium hydroxide solution and a potassium hydroxide solution.
[0025] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The above and / or additional aspects and advantages of the present invention will become clear and easily understood through the description of the embodiments in conjunction with the accompanying drawings, in which:
[0027] Figure 1 A graph showing the hydrogen production from five cycles of microwave pyrolysis of mixed plastics using multi-element nano-metal particles in Example 1 of the present invention;
[0028] Figure 2 A graph showing the hydrogen production from five cycles of microwave pyrolysis of mixed plastics using self-derived carbon nanotubes loaded with multi-element nano-metal particles according to Example 2 of the present invention;
[0029] Figure 3 The transmission electron microscope spectrum of the purified and activated carbon nanotubes prepared in Example 2 of the present invention is shown. DETAILED DESCRIPTION
[0030] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0031] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0032] In a first aspect of the present invention, the present invention provides a method for preparing high-purity hydrogen from waste plastic self-derived carbon nanotubes, comprising:
[0033] S1. Mixing plastic and a multi-element nano-metal catalyst, adding a microwave absorber, and obtaining a mixture, wherein the multi-element nano-metal catalyst comprises Ni, Al, and Fe.
[0034] In some embodiments of the present invention, the microwave absorber includes carbon-based microwave absorbers such as silicon carbide, activated carbon, graphite, carbon black, etc. The microwave absorber can convert microwave energy into energy of molecular motion, and convert it into heat energy through the dissipation of the motion, thereby enhancing the microwave effect and assisting in the preparation of hydrogen with high yield and purity.
[0035] Plastics are generally waste plastics, including single or mixed polyethylene, low-density polyethylene, high-density polyethylene, polystyrene, polypropylene, polyethylene terephthalate, polyvinyl chloride, etc.
[0036] In some embodiments of the present invention, the mass ratio of the plastic to the microwave absorber is 1:(2-10), for example, it can be 1:2, 1:5, 1:6, 1:10, etc. Controlling the mass ratio of the two within the above range is conducive to fully absorbing microwaves, thereby improving the decomposition effect of the plastic and preparing hydrogen with high yield and purity.
[0037] In some embodiments of the present invention, the particle size of the microwave absorber is 3mm-10mm, for example, it can be 3mm, 5mm, 7mm, 9mm, 10mm, etc. Therefore, by controlling the average particle size of the microwave absorber within the above range, microwaves can be effectively absorbed and converted into thermal energy, thereby further improving the decomposition effect of the plastic and preparing hydrogen with high yield and purity.
[0038] In some embodiments of the present invention, the mass ratio of the multi-element nano-metal catalyst to the plastic is 1:(0.5-2.5), for example, 1:05, 1:1, 1:2, 1:2.5, etc. Controlling the mass ratio of the multi-element nano-metal catalyst to the plastic within the above range is conducive to the multi-element nano-metal catalyst absorbing microwaves and heating up quickly, fully catalyzing the plastic to decompose it, and preparing hydrogen with high yield and purity.
[0039] In some embodiments of the present invention, in the multi-nanometallic catalyst, the molar ratio of Ni, Al and Fe is 1:(1-5):(1-5), for example, it can be 1:1:1, 1:3:3, 1:5:5, etc., thereby controlling the mass ratio of the three within the above range, the catalytic activity of the multi-nanometallic catalyst is high, which is beneficial for the multi-nanometallic catalyst to fully catalyze the decomposition of the plastic and prepare hydrogen with high yield and purity.
[0040] In some embodiments of the present invention, the multi-element nanometal catalyst is prepared by the following method:
[0041] Dissolve soluble nickel salt, soluble aluminum salt and soluble iron salt in water, add chelating agent, heat and stir to form gel;
[0042] The gel is dried and calcined to obtain a multi-element nano-metal catalyst.
[0043] The multi-element nano-metal catalyst prepared by the sol-gel method has good dispersibility and nano-scale particles. The three metals Ni, Al and Fe are evenly mixed, which makes the catalytic activity of the multi-element nano-metal catalyst high, which is conducive to the multi-element nano-metal catalyst to fully catalyze the decomposition of plastic and prepare hydrogen with high yield and purity.
[0044] In some embodiments of the present invention, the chelating agent includes at least one of citric acid, urea, polyethylene glycol, and ethylenediaminetetraacetic acid. The above chelating agents can form complexes with soluble nickel salts, soluble aluminum salts, and soluble iron salts in the solution, so that in the subsequent calcination process, the three metals Ni, Al, and Fe are evenly mixed, so that the catalytic activity of the multi-nanometallic catalyst is high, which is beneficial for the multi-nanometallic catalyst to fully catalyze the decomposition of the plastic and prepare hydrogen with high yield and purity.
[0045] In some embodiments of the present invention, the heating temperature is 80°C-120°C, for example, it can be 80°C, 90°C, 100°C, 120°C. Controlling the heating temperature within the above range is conducive to the formation of complexes among soluble nickel salts, soluble aluminum salts and soluble iron salts, and turning them into a gel state, so that in the subsequent calcination process, the three metals Ni, Al and Fe are evenly mixed.
[0046] In some embodiments of the present invention, the stirring time is 2h-6h. For example, the stirring time can be 2h, 3h, 4h, 5h, 6h, etc. Controlling the stirring time within the above range is conducive to uniform mixing of the soluble nickel salt, the soluble aluminum salt and the soluble iron salt to form a gel-like complex.
[0047] In some embodiments of the present invention, the mass ratio of the soluble nickel salt, the soluble aluminum salt and the soluble iron salt is 1:(1-8):(1-8), for example, it can be 1:1:1, 1:5:1, 1:6:6, 1:6:8, etc. Controlling the ratio of the three within the above range is conducive to obtaining a multi-nanometallic catalyst with a molar ratio of Ni, Al and Fe in the range of 1:(1-5):(1-5), so that the catalytic activity of the multi-nanometallic catalyst is high, which is conducive to the multi-nanometallic catalyst to fully catalyze the decomposition of waste plastics and prepare hydrogen with high yield and purity.
[0048] In some embodiments of the present invention, the calcination temperature is 350°C-650°C, for example, it can be 350°C, 450°C, 650°C. Controlling the calcination temperature within the above range is conducive to the redox reaction of the complex, activating the surface active sites, and then obtaining a multi-nanometallic catalyst, which is conducive to fully catalyzing the decomposition of the plastic and preparing hydrogen with high yield and purity.
[0049] In some embodiments of the present invention, waste plastics, including single or mixed polyethylene, low-density polyethylene, high-density polyethylene, polystyrene, polypropylene, polyethylene terephthalate, polyvinyl chloride, etc., are pretreated and impurities on the surface of the waste plastics are cleaned with water.
[0050] S2, heating the mixture in an inert gas by microwave to obtain hydrogen and self-derived carbon nanotubes;
[0051] The method for preparing hydrogen from plastic proposed by the present invention adopts a microwave heating method and uses a multi-element nano-metal catalyst containing Ni, Al and Fe to increase the temperature of the internal particles, thereby promoting molecular motion and heat transfer by forming a local temperature rise area, and obtaining a higher yield of gas products and a high value-added solid product. In addition, the carbon nanotube solid product formed by microwave heating can also be used as a carrier of the multi-element nano-metal catalyst after activation and purification, and has a stronger microwave absorption effect, catalytic activity and stability, so that the obtained hydrogen yield and purity are both higher, and the multi-element nano-metal particle catalyst can be recycled ten times, so that this catalyst has a higher economic value.
[0052] In some embodiments of the present invention, the power of the microwave heating is 1kW-3kW, for example, 1kW, 2kW, 3kW, etc. By controlling the power of the microwave heating within the above range, the plastic can be fully heated and decomposed, thereby improving the decomposition effect of the plastic and preparing hydrogen with high yield and purity.
[0053] In some embodiments of the present invention, the microwave heating temperature is 450°C-750°C. For example, it can be 450°C, 500°C, 600°C, 700°C, 750°C, etc. By controlling the microwave heating temperature within the above range, the plastic can be fully heated and decomposed, thereby improving the decomposition effect of the plastic and preparing hydrogen with high yield and purity.
[0054] In some embodiments of the present invention, the microwave heating time is 10 min-50 min, for example, it can be 10 min, 20 min, 30 min, 40 min, 50 min, etc. Therefore, by controlling the microwave heating time within the above range, the plastic can be fully heated and decomposed, thereby improving the decomposition effect of the plastic and preparing hydrogen with high yield and purity.
[0055] In some embodiments of the present invention, the above catalyst is mixed with waste plastic in a weight ratio of 1:1 and added to a microwave reactor. Microwave generators are placed at the bottom (2kW) and the right side (1kW). The microwave power can be adjusted steplessly from 1kW to 3kW. The microwave frequency is 2.45GHz.
[0056] In some embodiments of the present invention, the above catalyst and waste plastic are placed in a quartz container, purged with nitrogen before the microwave pyrolysis experiment begins, and then reacted for 10-50 minutes using a microwave power of 2kW-3kW until no gas is generated.
[0057] S3, reloading the self-derived carbon nanotubes with the multi-element nano-metal catalyst added in step S1, and reacting by microwave heating in step S2 to obtain hydrogen. The method for preparing hydrogen by enhancing microwave effect of waste plastic self-derived carbon nanotubes proposed in the present invention further increases the hydrogen production by more than 20% to 62.55 mmol / g, and the hydrogen purity is greater than 90 vol%.
[0058] According to experimental measurements, the gas produced by plastics is a mixture of hydrogen, methane, carbon dioxide, carbon monoxide, ethylene and ethane. Hydrogen is the main gas, accounting for 90 vol%, reaching a medium purification level equivalent to some membrane technologies. The generated gas can also be processed by a gas purification device, and hydrogen with a purity of >99.9999% can be obtained.
[0059] In some embodiments of the present invention, step S2 comprises:
[0060] S21, heating the mixture by microwave in an inert gas to obtain a hydrogen mixed gas, a solid product, and a liquid oil;
[0061] S22, treating the solid product with an acid solution, washing it to neutrality, and then treating it with an alkaline solution, washing it to neutrality, to obtain activated carbon nanotubes;
[0062] Step S3 includes:
[0063] S31, dissolving a soluble nickel salt, a soluble aluminum salt and a soluble iron salt in water, adding the activated carbon nanotubes and a chelating agent, heating and stirring to form a gel;
[0064] S32, drying and calcining the gel to obtain a multi-element nano-metal catalyst supported by self-derived carbon nanotubes;
[0065] S33, using the self-derived carbon nanotube multi-nanometallic catalyst in steps S1 and S21 to further prepare hydrogen.
[0066] Thus, the activated carbon nanotubes are obtained, which have more active edge sites on the outer surface, are helpful for loading metal Ni, Al and Fe, and can prepare highly active catalysts. The self-derived carbon nanotubes loaded with multi-element nano-metal particles obtained by the present invention have stronger microwave absorption effect, catalytic activity and stability, and can obtain hydrogen with high purity and yield. In addition, the multi-element nano-metal particle catalyst loaded with self-derived carbon nanotubes can be recycled ten times, so that the catalyst has a high economic value.
[0067] By using the self-derived carbon nanotube catalyst to react with plastic in a microwave environment, the complete conversion of hydrogen elements can be achieved, and 99% of it can be converted into gaseous hydrogen-containing substances. The hydrogen production can reach 62.55mmol / g, and the hydrogen purity can reach 90vol%.
[0068] By using self-derived carbon nanotubes loaded with multi-element nano-metal particles, the hydrogen production was increased by more than 20% compared with the catalyst without carbon nanotubes, and the hydrogen utilization efficiency reached more than 99%. The hydrogen purity reached 90vol%. In the first five cycles, the hydrogen purity was between 88vol% and 92vol%. In the 6th to 10th cycles, the hydrogen purity decreased slightly, but still reached more than 83vol%.
[0069] In some embodiments of the present invention, the mass ratio of carbon nanotubes to acid solution is 1:(100-150).
[0070] In some embodiments of the present invention, the activated carbon nanotubes have a cup-shaped morphology. The cup-shaped carbon nanotube product has more active edge sites on the outer surface, which is helpful for loading metals and preparing highly active catalysts. In addition, the defect structure with this unique shape is more conducive to regulating the dielectric properties of the activated carbon nanotubes, and can achieve an appropriate balance between good impedance matching and strong loss capacity.
[0071] In some embodiments of the present invention, the mass of the activated carbon nanotubes accounts for 10%, 15%, 25% of the mass of the multi-nanometallic catalyst loaded on the self-derived carbon nanotubes, for example. Controlling the mass proportion of the activated carbon nanotubes within the above range is further beneficial to improving the catalytic activity of the self-derived carbon nanotube multi-nanometallic catalyst, which is beneficial to fully catalyze the decomposition of the plastic and prepare hydrogen with high yield and purity.
[0072] In some embodiments of the present invention, the acid solution includes at least one of concentrated nitric acid, concentrated sulfuric acid, and hydrochloric acid. The residue is treated with the above acid solution to fully remove impurities in the carbon nanotubes, activate the carbon nanotubes, and enhance their edge active sites, which is beneficial to loading multi-nanometallic particles, enhancing catalytic activity, and preparing hydrogen with high yield and purity.
[0073] In some embodiments of the present invention, the alkaline solution includes at least one of a sodium hydroxide solution and a potassium hydroxide solution. The alkaline solution used to treat the carbon nanotubes can fully remove impurities therein, activate the carbon nanotubes, and enhance the catalytic activity of the multi-element nano-metal catalyst, which is conducive to the multi-element nano-metal catalyst fully catalyzing the decomposition of the plastic and preparing hydrogen with high yield and purity.
[0074] In summary, the present invention utilizes carbon nanotubes self-derived during the reaction process, which are purified and activated as a matrix, and then loaded with multi-element nanoparticles (Ni / Al / Fe based) as a catalyst to further enhance the microwave reaction and catalytically degrade mixed waste plastics to prepare pure high-purity hydrogen. This method solves the problem of low hydrogen yield and purity in traditional plastic pyrolysis, and recycles the self-derived carbon nanotubes.
[0075] The scheme of the present disclosure will be explained below in conjunction with the examples. Those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. Where specific techniques or conditions are not indicated in the examples, the techniques or conditions described in the literature in this area or the product instructions are used. Where the manufacturers of reagents or instruments are not indicated, they are all conventional products that can be obtained commercially.
[0076] Example 1
[0077] 25 g Fe(NO 3 ) 3 9H 2 O, 25g Al(NO 3 ) 3 9H 2 O and 15 g Ni(NO 3 ) 2 6H 2 O, 12g of anhydrous citric acid was dissolved and mixed. Heat and stir at 80°C under a magnetic stirrer for 4 hours to make it a viscous gel. Then put it in a 105°C oven to dry overnight. Finally, the dried sample was calcined in a muffle furnace for 3 hours, and the temperature was raised from room temperature to 450°C at a heating rate of 10°C / min. After taking it out and grinding, a Ni-Al-Fe multi-metal nanocatalyst was obtained.
[0078] Mix 1g of the above catalyst, 1g of waste plastic (40% low-density polyethylene, 40% high-density polyethylene polypropylene, 20% polypropylene) and 2g of microwave absorbent silicon carbide particles with a particle size of 5mm. Add them into a quartz reaction container. Set the microwave power to 2kW and the microwave frequency to 2.45GHz. When the temperature rises to 550℃, keep it for 10 minutes and collect the gas product in a 10L air bag. Then wait for the reaction container to cool to room temperature.
[0079] After the solid product was cooled, it was weighed and 1g of the plastic mixture was added to it and mixed with it. The experiment was repeated 5 times. The hydrogen production was detected by gas phase GC. Figure 1 After each reaction, the solid product was collected.
[0080] from Figure 1 It can be seen that in the method of Example 1 of the present application, after the catalyst is circulated 5 times, the amount of hydrogen generated is still relatively high.
[0081] Example 2
[0082] After three parallel experiments were performed on Example 1, the solid product residue (about 1.2 g) was collected, and then the solid product was purified and activated using an acid-base mixed method:
[0083] The solid product was placed in a centrifuge tube and 30 ml of HNO 3 and 90ml H 2 SO 4 . After ultrasonic dispersion for 1 hour, let it stand for 4 hours. Then vacuum filter and wash repeatedly until it becomes neutral, then add 3 mol / L NaOH aqueous solution at a ratio of 1:100 of carbon nanotube solid mass: NaOH solution mass, and ultrasonically disperse for one hour. Then vacuum filter and wash repeatedly until it becomes neutral, and dry in an oven at 105°C overnight.
[0084] The activated carbon nanotubes (0.3 g) were purified and added to 30 ml of deionized water.
[0085] 25 g Fe(NO 3 ) 3 9H 2 O, 25g Al(NO 3 ) 3 9H 2 O and 15 g Ni(NO 3 ) 2 6H 2 0.12g of anhydrous citric acid was dissolved and mixed, and then mixed with deionized water containing purified activated carbon nanotubes. Heat and stir under a magnetic stirrer at 80°C for 4 hours to make it a viscous gel. Then put it in a 105°C oven to dry overnight. Finally, the dried sample was calcined in a muffle furnace for 3 hours, and the temperature was raised from room temperature to 450°C at a heating rate of 10°C / minute. After taking it out and grinding, a multi-metal nanocatalyst loaded with self-derived carbon nanotubes was obtained.
[0086] 1g of the above catalyst, 1g of waste plastic (40% low-density polyethylene, 40% high-density polyethylene polypropylene, 20% polypropylene) and 2g of microwave absorbent silicon carbide particles with a particle size of 5mm were mixed evenly. Added into a quartz reaction vessel. The microwave power was set to 2kW, and when the temperature was raised to 550°C, it was maintained for 10 minutes, and the gas products were collected in a 10L air bag to test the catalytic reaction performance. Through gas phase GC detection, in this embodiment, the hydrogen production was increased by 20% compared with Example 1, reaching 62.55mmol / g plastic, and the volume was about 90vol%.
[0087] After the solid product was cooled, it was weighed and 1g of the plastic mixture was added to it and mixed with it. The cycle experiment was repeated 5 times. The hydrogen production was as follows: Figure 2 As shown, it can be seen that the hydrogen production and stability are better than the original Ni-Al-Fe multi-element nanometal catalyst in Example 1.
[0088] Figure 3 This is the transmission electron microscope spectrum of the purified and activated carbon nanotubes in Example 2. It can be seen that the metal catalyst at the end of the carbon nanotube has been purified and has obvious openings, which is conducive to the subsequent loading of multi-element nano-metal particles. Secondly, the dispersion of the purified and activated carbon nanotubes is improved, which reduces the adverse effects of the reduction in the specific surface area of the catalyst carrier, the change in pore structure, and the reduction in the exposure of active sites due to the entanglement / agglomeration of the carbon nanotubes.
[0089] Example 3
[0090] Oxygen-containing waste plastic (polyethylene terephthalate) and foamed waste plastic (polystyrene) were added to the mixed waste plastic raw material, and other conditions were the same as those in Example 2. The feasibility of this method and the self-derived carbon nanotube multi-metal catalyst in preparing high-purity hydrogen in oxygen-containing mixed waste plastic was verified.
[0091] 1g of self-derived carbon nanotube multi-metal catalyst (prepared in the same manner as in Example 2), 1g of waste plastic (28% low-density polyethylene, 28% high-density polyethylene polypropylene, 30% polypropylene, 7% polyethylene terephthalate, 7% polystyrene) and 2g of microwave absorbent silicon carbide particles with a particle size of 5mm were mixed evenly and added into a quartz reaction container. The reaction conditions were the same as in Example 2.
[0092] Through gas phase GC detection, in this embodiment, the hydrogen production reached 54.67mmol / g plastic, with a volume of about 89.57vol%. The hydrogen production was slightly reduced compared with that in Example 2 because the theoretical hydrogen production value of oxygen-containing mixed waste plastics decreased. However, the high purity of hydrogen was still maintained, verifying the feasibility of preparing high-purity hydrogen from oxygen-containing mixed waste plastics with multi-metal catalysts supported by self-derived carbon nanotubes.
[0093] Example 4
[0094] Chlorine-containing waste plastics (polyvinyl chloride) and foamed waste plastics (polystyrene) were added to the mixed waste plastic raw materials, and other conditions were consistent with Example 2. The feasibility of this method for preparing high-purity hydrogen from chlorine-containing mixed waste plastics was verified, and the problem of difficult disposal of chlorine-containing waste plastics was solved.
[0095] 1g of self-derived carbon nanotube multi-metal catalyst (prepared in the same manner as in Example 2), 1g of waste plastic (28% low-density polyethylene, 28% high-density polyethylene polypropylene, 30% polypropylene, 7% polyvinyl chloride, 7% polystyrene) and 2g of microwave absorbent silicon carbide particles with a particle size of 5mm were mixed and added to a quartz reaction container. The reaction conditions were the same as in Example 2.
[0096] Through gas phase GC detection, in this embodiment, the hydrogen production reached 50.93mmol / g plastic, and the volume was about 84.78vol%. Compared with the hydrogen production in Example 2, it was slightly reduced because the theoretical hydrogen production value of chlorine-containing mixed waste plastics decreased, but still maintained a high hydrogen purity.
[0097] Examples 2-4 verify that this method and the self-derived carbon nanotube multi-metal catalyst of this invention have good feasibility. A method for preparing high-yield and high-purity hydrogen by treating mixed oxygen-containing / chlorine-containing mixed waste plastics is invented.
[0098] Comparative Example 1
[0099] 15 g Ni(NO 3 ) 2 6H 2 O metal salts were replaced by Co(NO 3 ) 3 9H 2 O, and the remaining steps are consistent with Example 1 to prepare Co-Al-Fe multinary nano-metal particles. At the same time, four metals, Fe, Ni, Co, and Al, are combined into binary metal catalysts to compare their hydrogen production effects, as shown in Table 1 below. The results show that the Ni-Al-Fe multinary nano-metal particles prepared by the present invention have the highest hydrogen production.
[0100] Table 1 Effect of different nano-metal particles on hydrogen production from waste plastics
[0101]
[0102] In summary, the method for preparing hydrogen from waste plastic self-derived carbon nanotubes proposed in the present invention adopts a microwave heating method and uses a multi-element nanometal catalyst containing Ni, Al and Fe to obtain hydrogen with high yield and purity.
[0103] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", "some implementation schemes" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0104] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing high-purity hydrogen from waste plastic self-derived carbon nanotubes, characterized in that: include: S1. mixing plastic and a multi-element nano-metal catalyst, and adding a microwave absorber to obtain a mixture, wherein the multi-element nano-metal catalyst comprises Ni, Al and Fe; S2, heating the mixture in an inert gas by microwave to obtain hydrogen and self-derived carbon nanotubes; S3, reloading the self-derived carbon nanotubes with the multi-element nano-metal catalyst added in step S1, and reacting by microwave heating in step S2 to obtain hydrogen.
2. The method according to claim 1, characterized in that The microwave absorber comprises at least one of silicon carbide, activated carbon, graphite and carbon black; and / or, The mass ratio of the plastic to the microwave absorber is 1:(2-10).
3. The method according to claim 1 or 2, characterized in that: The particle size of the microwave absorbent is 3 mm to 10 mm; and / or, The mass ratio of the multi-element nano-metal catalyst to the plastic is 1:(0.5-2.5); and / or, In the multi-element nanometal catalyst, the molar ratio of Ni, Al and Fe is 1:(1-5):(1-5).
4. The method according to claim 1 or 2, characterized in that: The multi-element nano-metal catalyst is prepared by the following method: Dissolve soluble nickel salt, soluble aluminum salt and soluble iron salt in water, add chelating agent, heat and stir to form gel; The gel is dried and calcined to obtain a multi-element nano-metal catalyst.
5. The method according to claim 4, characterized in that The chelating agent includes at least one of citric acid, urea, polyethylene glycol, and ethylenediaminetetraacetic acid; and / or, The heating temperature is 80°C-120°C; and / or, The stirring time is 2h-6h; and / or, The calcination temperature is 350°C-650°C; and / or, The mass ratio of the soluble nickel salt, the soluble aluminum salt and the soluble iron salt is 1:(1-8):(1-8).
6. The method according to claim 1 or 2, characterized in that: The power of the microwave heating is 1kW-3kW; and / or, The microwave heating temperature is 450°C-750°C; and / or, The microwave heating time is 10 min-50 min.
7. The method according to claim 1 or 2, characterized in that: Step S2 includes: S21, heating the mixture by microwave in an inert gas to obtain a hydrogen mixed gas, a solid product, and a liquid oil; S22, treating the solid product with an acid solution, washing it to neutrality, and then treating it with an alkaline solution, washing it to neutrality, to obtain activated carbon nanotubes; Step S3 includes: S31, dissolving a soluble nickel salt, a soluble aluminum salt and a soluble iron salt in water, adding the activated carbon nanotubes and a chelating agent, heating and stirring to form a gel; S32, drying and calcining the gel to obtain a multi-element nano-metal catalyst supported by self-derived carbon nanotubes; S33, using the self-derived carbon nanotube multi-nanometallic catalyst in steps S1 and S21 to further prepare hydrogen.
8. The method according to claim 7, characterized in that The activated carbon nanotubes have a cup-stacked morphology.
9. The method according to claim 7, characterized in that: The mass of the activated carbon nanotubes accounts for 10%-40% of the mass of the multi-nanometallic catalyst supported by the self-derived carbon nanotubes.
10. The method according to claim 7, characterized in that In step S22, the acid solution includes at least one of concentrated nitric acid, concentrated sulfuric acid, and hydrochloric acid; and / or, In step S22, the mass ratio of the solid product to the acid solution is 1:(100-150); In step S22, the alkaline solution includes at least one of a sodium hydroxide solution and a potassium hydroxide solution.
Citation Information
Patent Citations
Preparation method of nitrogen-doped carbon nanotubes with cup stacked structures
CN113788470A
Method and device for preparing hydrogen and multi-walled carbon nanotubes by microwave pyrolysis of waste plastics
CN115432663A
Few-wall array carbon nanotube as well as growth catalyst precursor and preparation method thereof
CN115536007A
Composite microwave absorbent of Nano carbon tube, and preparation method
CN1727306A
Carbon nanotube, a supported catalyst comprising thesame, and fuel cell using the same
KR100745736B1